2020
DOI: 10.1002/adem.202000194
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electron Beam Melting of TiAl Alloy: Metallurgical Defects, Tensile Property, and Determination of Process Window

Abstract: Selective electron beam melting (SEBM) is a promising method to manufacture complex titanium aluminide (TiAl) alloy parts. Herein, the effects of beam current, scanning speed and energy density on surface appearance, porosity, and Al loss of Ti–47Al–2Cr–2Nb alloy samples fabricated by SEBM are investigated systematically. The porosity decreased initially and then increased, and Al loss increased gradually with an increase in beam current. The porosity increased continuously and the Al loss decreased gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…which additionally considers the line offset l offset as the distance between adjacent hatch lines and the layer thickness t. [18] In many cases, a higher E V was found to be associated with a reduction in part porosity. [19][20][21] A correlation between process energy input and further component properties, such as surface morphology, [22][23][24][25] microstructure, [4,26,27] or evaporation of alloying elements, [28][29][30] was also observed by several authors. It is generally accepted that insufficient energy density results in small melt pool dimensions and low melt pool temperatures, [23,31] which in turn lead to unmelted powder particles [16] and lack-of-fusion defects [13] between the individual layers.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…which additionally considers the line offset l offset as the distance between adjacent hatch lines and the layer thickness t. [18] In many cases, a higher E V was found to be associated with a reduction in part porosity. [19][20][21] A correlation between process energy input and further component properties, such as surface morphology, [22][23][24][25] microstructure, [4,26,27] or evaporation of alloying elements, [28][29][30] was also observed by several authors. It is generally accepted that insufficient energy density results in small melt pool dimensions and low melt pool temperatures, [23,31] which in turn lead to unmelted powder particles [16] and lack-of-fusion defects [13] between the individual layers.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, other parameter combinations with a similar E V produced equiaxed microstructures. Yue et al [21] outlined that the use of different scan velocities at the same energy density leads to different beam return times, which in turn affects the thermal boundary conditions. The beam return time t R is defined as the time required for the electron beam to return to the same point in the adjacent line and can be calculated according to Equation (3) as the ratio of the scan length L and the scan velocity v scan [22] t…”
Section: Introductionmentioning
confidence: 99%
“…But loss of Al elements during the manufacturing process was one of the main challenges for the SEBM process. [19][20][21] Compared with SEBM, LPBF technique enabled to fabricate γ-TiAl parts with higher dimensional accuracy. However, like other high-strength or brittle materials, [22][23][24] the most critical challenge in LPBF of γ-TiAl alloys was to increase the printability because these types of alloys had high cracking susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam melting (EBM) technology is a kind of additive manufacturing technology widely used in the aerospace field, which can form high-performance metal parts with complex shapes [1][2][3][4][5][6][7]. Titanium alloy is one of the most widely investigated and used materials in EBM.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructures and mechanical properties of TiAl-based alloys were also discussed and investigated by numerous investigations. Yue et al [7,37,38] investigated the process window, defects, microstructures, heat treatment as well as tensile properties at room and elevated temperatures of Ti-47Al-2Cr-2Nb alloy. Wimler et al [39] reported the development of novel process-adapted γ-TiAl based alloys, showing that it was possible to produce reliable high-performance TiAl components by the use of proper parameters in combination with subsequent heat treatments.…”
Section: Introductionmentioning
confidence: 99%